The Case for the Extra-Territorial Application of Corporate Governance Standards in China - Bryane Michael; Say-Hak Goo (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
What rule might an international financial centre like Hong Kong play in incentivizing corporate governance reform in China? Or any foreign jurisdiction? In this article, we describe theoretical application of extra-territoriality to corporate governance related law in Hong Kong. We describe why and how such extra-territoriality (following the US's lead) could encourage Mainland firms to adopt better corporate governance practices (and even implement them). Changes to the Companies Ordinance and the Hong Kong Stock Exchange's Listing Rules can, in theory, provide for such extra-territorial reach. The results of such an experiment would help us understand the role an international financial centre can play in creating value across borders, as well as make Hong Kong's rules and markets more relevant in/to the Mainland.
Keywords: 330; extra-territoriality; Hong Kong Listing Rules; Chinese corporate governance